واقع وتحديات السياحة الصحراوية دراسة تحليلية للفترة 2015-2024 بولاية غرداية -الجزائر - برهان, نورالدين (مجلـة إضافات اقتصادية, 2026)
Keywords: Tourisme -- Mzab

The Role of Marketing-Oriented Urban Planning and Design in Enhancing a City's Visual Image: A Case Study of Ghardaïa City - Boukerch, Abdelkader; Abidi, Fatiha (Journal of Business Administration and Economic Studies, 2025)
This research examines the strategic role of marketing-oriented urban planning and design in enhancing the city's visual image, using Ghardaïa, a UNESCO World Heritage city in southern Algeria, as a case study. The study highlights the problem of the city's eroding visual image, which is a result of the poor integration between urban planning and city marketing. The clarity of a city's visual image generally reflects the interaction between its urban formation elements—buildings, urban blocks, and internal and external spaces—and the background of the visual scene, such as topography and climate. However, the focus of this study is on the formative structure of the city's visual image, which is the combination of physical planning elements and the natural background. This can be conceptualized as the sum of two mathematical functions influenced by a primary variable, time (t). This is not necessarily a quantitative measurement of the visual image's clarity, but rather a qualitative assessment and interpretation of this image's significance, achieved by using strategic urban planning, innovative architectural design, and an effective marketing mix.
Keywords: Tourisme -- Mzab; Urbanisme -- Mzab

Tourisme saharien : Afflux croissant à ghardaïa - H., Nabil (El Watan, 2025)
Keywords: Tourisme -- Mzab

Promotion du tourisme dans le sud du pays : Une caravane de tour-opérateurs algériens et étrangers dans le M’zab - APS (El Watan, 2024)
Keywords: Tourisme -- Mzab

A la decouverte du M’zab et Timimoun : Immersion dans deux joyaux du Sud - Benelkadi, Kamel (El Watan, 2024)
Keywords: Tourisme -- Mzab

Patrimoine culturel algérien: Un trésor à valoriser et à préserver - Belabed, Samira (Sud Horizons, 2024)
Keywords: Tourisme -- Mzab

Tourisme saharien : Priorite a la rehabilitation de la route des Ksour - Mehdid, A. (Sud Horizons, 2023)
Keywords: Tourisme -- Mzab

Ghardaia Heritage Attractions: A Significant Sector in the Algerian Tourism Industry - Almi, Hanane; Seriou, Cheikh (2023)
This paper attempts to highlight the growing significance of heritage tourism. It begins by defining some notions and concepts in relation to the scope of the work including tangible and intangible heritage. It tries, then, to identify some issues endangering heritage, and it presents some measures to preserve and promote it. The study moves forward to address the local heritage. Known for its natural, historical, architectural, and cultural assets, Ghardaia is considered one of the most fascinating Algerian heritage destinations that attract tourists and researchers interested in exploring North African and Islamic culture. The culture in Ghardaia is deeply rooted in tradition, and the province has a rich history of sophisticated arts, crafts, carpets, clothes, music, oases,festivals, and different cultural practices that have been passed down through generations. It is a UNESCO World Heritage Site renowned for its distinctive buildings constructed in intricate geometrical patterns forming fortified villages, or ksour. Like many desert regions, Ghardaia offers a portrait of a distinct and well-preserved way of life in a harsh arid environment
Keywords: Tourisme -- Mzab